2015
DOI: 10.3941/jrcr.v9i4.1869
|View full text |Cite
|
Sign up to set email alerts
|

18-FDG Uptake in Pulmonary Dirofilariasis

Abstract: Solitary pulmonary nodules are a common finding on chest radiography and CT. We present the case of an asymptomatic 59-year-old male found to have a 13 mm left upper lobe nodule on CT scan. The patient was asymptomatic and the CT was performed to follow up mediastinal and hilar lymphadenopathy that had been stable on several previous CT scans. He had a history of emphysema and reported a 15 pack-year smoking history. PET-CT was performed which demonstrated mild 18-FDG uptake within the nodule. Given his age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Usually in the chest X ray a subpleural pulmonary nodule sized 1-3 cm with well-defined margins is diagnosed. The lesions are usually detected at the right lower lobe (1,8). However, the pulmonary nodules can be multiple or bilateral (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually in the chest X ray a subpleural pulmonary nodule sized 1-3 cm with well-defined margins is diagnosed. The lesions are usually detected at the right lower lobe (1,8). However, the pulmonary nodules can be multiple or bilateral (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, this examination showed no uptake of 18-fluorodeoxyglucose (18-FDG). Stone et al and Kang et al reported each of one case of HPD that both showed a mild uptake of 18-FDG (4,8). Other examination, such as angiography of the right side of the heart and pulmonary artery, transthoracic needle aspiration, examination of bronchial washings and biopsy or sputum cytology do not assist the diagnosis of the disease (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Western Europe, D. immitis is widespread causing severe cardiac signs in dogs [ 20 , 23 ]. In humans, pulmonary localizations of this parasite are observed [ 24 ], but the focal lesion in the lungs is often initially misdiagnosed as a tumor [ 23 ]. There are limited observations of other localizations of this parasite in humans, such as the chest, usually discovered in the course of coronary angiography [ 19 ], spermatic cord [ 17 ], scrotum [ 1 , 6 , 10 , 15 , 26 ], oral area [ 3 , 9 ], ovaries [ 16 ], liver [ 11 ], or subcutaneous tissue [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Введение. Дирофиляриоз человека -паразитарное заболевание, трансмиссивный гельминтоз, вызванный паразитированием нематод рода Dirofilaria, чаще всего D. repens и D. immitis, которое протекает с преимущественным поражением кожи (63%), конъюнктивы (50%), слизистых оболочек, подкожной клетчатки, реже -внутренних органов, из которых наиболее часто поражаются легкие [1,2,3]. В организме человека самки Dirofilaria способны достигать половой зрелости, но не могут размножаться микрофилярии, поэтому человек не может являться распространителем данного заболевания [4,5].…”
unclassified